The Demand for, and Impact of, Youth Internships : Evidence from a Randomized Experiment in Yemen - McKenzie, David; Assaf, Nabila; Cusolito, Ana Paula (World Bank, Washington, DC, 2016)
This paper evaluates a youth internship program in Yemen. The authors examine the demand for the program, and find an oversupply of graduates in science, technology, engineering, and mathematics, and a relative undersupply of graduates in marketing and business. Conditional on the types of graduates firms were looking to hire, applicants were then randomly chosen for the program. Receiving an internship resulted in an almost doubling of work experience in 2014, and a 73 percent increase in income. A follow-up survey shows that internship recipients had better employment outcomes than the control group in the first five months after the program.